RESEÑA de: García Roca, Javier ; Santolaya, Pablo (eds.). Europe of rights : a compendiumon the european convention of human rights. Leiden- Boston : Martinus Nijhoff Publishers , 2012. - Gordillo Pérez, Luis I. (Teoría y Realidad Constitucional, 2012)
La presente nota realiza una valoración crítica de la monografía coordinada por los profesores Roca y Santolaya titulada Europe of Rights: A Compendium on the European Convention of Human Rights. This article reviews the book edited by Professors Roca and Santolaya entitled Europe of Rights: A Compendium on the European Convention of Human.